Reaction mechanisms of H(D) → D(H) + Pt(111) interaction system: Quasiclassical molecular dynamics simulations - Vurdu, Can Doğan (AIP Publishing, 2021)
Reaction mechanisms of the H(or D) → D(or H) + Pt(111) interaction system have been proposed by using quasiclassical molecular dynamics simulations. First, the adsorbate atoms are dispersed randomly over the surface’s adsorption sites to form 0.18 ML, 0.25 ML, and 0.50 ML of coverages. Since the surface is considered to be resilient, thanks to imitating the multi-layer slab by using a function of many-body embedded-atom potential energy, the slab atoms can move because of the implemented external forces. Thus, energy transfer from the incident atom to surface atoms and adsorbates has been considered a real collision system. Moreover, the London–Eyring–Polanyi–Sato function is modified to model interaction between the adsorbates and slab atoms. In addition to desorption of HD and H2(or D2) after the collision of the incoming H(or D) atom with the surface, subsurface penetration, sticking on the surface, and inelastic reflection of the incident atom have been investigated in detail as the reaction mechanisms on the surface. In addition, isotopic effects on reaction mechanisms have been analyzed in depth and shown. Also, hot-atom and Eley–Rideal mechanisms have been examined and explained. The hot-atom mechanism is responsible for the formation of H2/D2 products. Furthermore, the sticking rate on the surface is lower than the rate of subsurface penetration.
Keywords: Physics; QC1-999; 7. Clean energy